PERSEPSI TENTANG PERILAKU SEKSUAL PRANIKAH DITINJAU DARI JENIS PENDIDIKAN - Aini, Nurul; Al-Akhda Aulia, Lailatuzzahro (ILMU PSIKOLOGI, 2018)
Each individual has a different perception on the stimulus they receive, even though the stimulus is the same but the result will be a different perception. With the existence of a cultural, social teachings, and beliefs will give meaning to the object captured individuals, and ultimately the individual components will play a role in determining the availability of an answer in the form of individual attitudes and behavior of the object exists. In Indonesia, this latter phenomenon that often occurs about sexuality among adolescents, premarital sex secant-will now become a natural part of the channel the expression of love and affection (dating). The type of high school education in Indonesia is Public Institutions or Institutions recognized by the school and Religious Education or MA. The purpose of this study was to determine differences in perceptions about premarital sexual behavior among students at the Institute of Public Education (SMA) with students at the Institute of Religious Education (MA).